Optimizing prophylactic treatment of migraine: Subtypes and patient matching - Michel Dib (Dove Medical Press, 2008)
Michel DibFédération du système nerveux central, Hôpital de la Salpêtrière, Assistance Publique- Hôpitaux de Paris, FranceAbstract: Advances in our understanding of the pathophysiology of migraine have resulted in important breakthroughs in treatment. For example, understanding of the role of serotonin in the cerebrovascular circulation has led to the development of triptans for the acute relief of migraine headaches, and the identification of cortical spreading depression as an early central event associated wih migraine has brought renewed interest in antiepileptic drugs for migraine prophylaxis. However, migraine still remains inadequately treated. Indeed, it is apparent that migraine is not a single disease but rather a syndrome that can manifest itself in a variety of pathological conditions. The consequences of this may be that treatment needs to be matched to particular patients. Clinical research needs to be devoted to identifying which sort of patients benefit best from which treatments, particularly in the field of prophylaxis. We propose four patterns of precipitating factors (adrenergic, serotoninergic, menstrual, and muscular) which may be used to structure migraine prophylaxis. Finally, little is known about long-term outcome in treated migraine. It is possible that appropriate early prophylaxis may modify the long-term course of the disease and avoid late complications.Keywords: migraine, diagnosis, treatment, prophylaxis, subtypes